DIGITAL SUPPORT SYSTEM FOR FULL-TIME AND REMOTE MASS INDIVIDUALIZED EDUCATION WITH ELEMENTS OF MACHINE LEARNING - Chirtsov, Aleksander; Mikushev, Vladimir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The requirements to the digital support system for opened individualized learning are formulated in the conditions of accelerated transition to remote forms. A version of a digital support system for development, search and provision of students with electronic educational resources in physics focused on the formation of individual trajectories of students in the educational space is considered. The possibility of several options for such a construction is allowed: 1) independent choice of the student; 2) the appointment of the trajectory by the teacher, supervisor or employer; 3) automated construction of trajectories by the system, organized on the basis of machine learning and artificial intelligence technologies.